Islamophobia: The Fault-lines amid Islam and the West - Hassan Farooq Mashwani, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The frequently triggering of perilous events around the world and their often connection with Islam is perceived as a terrifying threat to global peace and harmony. This threat perception is mostly linked to the phenomenon of Islamophobia. A large segment of the Western community developed a perception of prejudice about Muslims and Islam as a threat to tranquility of mankind that can eventually dwarf the entire global system. Such perception desperately affects the Muslim diaspora in the West and even elsewhere with discrimination for their physical appearances, dresses and religious practices. The Muslims minorities are labelled as terrorists, following the so called radical Islam, a sense of hatred and discrimination is shaping out against them among other societies. Such crucial incidents can be viewed as new fault-lines amid Islam and the Western world. The Organization of Islamic Conference along with some of the Muslim majority states; such as Turkey, Malaysia and Pakistan have started playing their role in educating both the Muslims and the West about the fault-lines of Islamophobia and its ultimate horrors for peace, stability and harmony world over.